The Angkorian world
1 online resource (xxiii, 661 pages)
Keywords: "The Angkorian World explores the history of Southeast Asia's largest ancient state from the first to mid-second millennium CE. Chapters by leading scholars combine evidence from archaeology, texts, and the natural sciences to introduce the Angkorian state, describe its structure, and explain its persistence over more than six centuries. Comprehensive and accessible, this book will be an indispensable resource for anyone studying premodern Asia. The volume's first of six sections provide historical and environmental contexts, discusses data sources, and the nature of knowledge production. The next three sections examine the anthropogenic landscapes of Angkor (agrarian, urban, and hydraulic), the state institutions that shaped the Angkorian state, and the economic foundations on which Angkor operated. Part V explores Angkorian ideologies and realities, from religion and nation to identity. The volume's last part reviews political and aesthetic Angkorian legacies in an effort to explain why the idea of Angkor remains central to its Cambodian descendants. Maps, graphics and photographs guide readers through the content of each chapter. Chapters in this volume synthesize more than a century of work at Angkor and in the regions it influenced. The Angkorian World will satisfy students, researchers, academics, and the knowledgeable layperson who seeks to understand how this great Angkorian Empire arose and functioned in the premodern world"--